The Essence of Program Design / Essence of Computing - Bell Douglas; Morrey Ian; Pugh John (Prentice Hall, 1997)
A complete introduction to the varied range of design methods that are available. Foreword, Acknowledgements, Preface, Introduction, Structured Programming, Functional Decomposition, The Michael Jackson Program Design Method, Data Flow Design, Object-Oriented Design, Formal Methods, Design Notations, Design Guidelines, Review, Index.